Checklist of the micro- and anophthalmic soil-dwelling weevils of the world (Coleoptera: Curculionidae) - Morrone, Juan J.; Hlaváč, Peter (Zootaxa, 2017)
A checklist of the soil-dwelling microphthalmic and anophthalmic weevils of the world is presented. A total of 485 species in 85 genera are recognised, distributed over eight subfamilies and 26 tribes. The subfamilies are arranged in the currently accepted phylogenetic sequence, whereas the tribes, genera and species are listed in alphabetical order. For each species, the type locality and the geographical distribution by country is provided. Particularly diversified taxa are Entiminae: Otiorhynchini (125 species), Brachycerinae: Raymondionymini (90 species), Cossoninae: Dryotribini (59 species), Cryptorhynchinae: Torneumatini (58 species) and Molytinae: Lymantini (39 species). The biogeographic region with the highest diversity of soil-dwelling weevils is the Palearctic, especially the circum-Mediterranean area, mostly because of the exploration effort that it has received, followed by the Ethiopian and Neotropical regions.